Double Palladium-Catalyzed Synthesis of Azepines - Božinović, Nina; Opsenica, Igor; Šolaja, Bogdan A. (Synlett, 2013)
The synthesis of new 5H-pyridobenzazepine and 5H-dipyridoazepine compounds using as key step a palladium-catalyzed amination–cyclization reaction is reported. By choosing an appropriate combination of ligands and reactants under standardized reaction conditions, N- and S-tricyclic products can be prepared in one step from the appropriate stilbenes.
Keywords: azepines; thiepines; palladium; double N- and S-arylation; fused heterocycles